Igai 'the Lord of the Oasis'. Issue 1 (June 2018) - Abruña Marti, Heri
This article discusses 28 attestations of Igai, 'the Lord of the Oasis', some of them overlooked in previous work on the god. After a survey of previous research, the question of his name will be briefly addressed, and a diachronic analysis of his attestations will be presented. A table summarising the attestations mentioned in the text can be found at the end of the article.